2017
DOI: 10.21608/epx.2017.11249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physicians’ smoking status on their knowledge, attitude, opinions and practices of smoking cessation in a University Hospital, in Egypt

Abstract: Background: The tobacco epidemic is one of the biggest public health threats. Smoking prevalence and smoking cessation intentions among physicians vary from a country/community to another. Recently, a global reduction in the rates of smoking among healthcare providers is observed. Aim: This study aims to describe the effect of physicians' smoking status on their knowledge, attitude, opinions, and practices of smoking cessation in patients in a Tertiary Healthcare University Hospital in Cairo, Egypt. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This is consistent with other studies that have shown that smoking habits among health care professionals correlate strongly with their attitudes toward providing SCTS practices. [32][33][34][35] We found that the scores for all the attitude variables were high and that the differences between the OH professionals were only small. The OH professionals had a positive attitude toward implementing more SCTS than they currently provided.…”
Section: Discussionmentioning
confidence: 68%
“…This is consistent with other studies that have shown that smoking habits among health care professionals correlate strongly with their attitudes toward providing SCTS practices. [32][33][34][35] We found that the scores for all the attitude variables were high and that the differences between the OH professionals were only small. The OH professionals had a positive attitude toward implementing more SCTS than they currently provided.…”
Section: Discussionmentioning
confidence: 68%
“…Reduction in tobacco use among tobacco users in general population was less compared to our study [Chertok. 20 : 38.3% decreased smoking and 21.3% decreased frequency; Streck et al 21 : 21.0% reported smoking less; Yingst et al 22 : 15% reported decrease in their tobacco use).]. Similarly, tobacco quit attempt was lower among the tobacco users in general population as reported by Chertok.…”
Section: Discussionmentioning
confidence: 88%
“…The proportion of HCPs (24.1%) in our study whose tobacco use did no change during the pandemic was very less compared to general population as reported by Chertok. 20 (43.3%), Streck et al 21 (44.0%) and Gupte et al 23 (70.0%). The HCPs are a special group and highly informed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, some studies have reported that the smoking status of physicians can affect their role in offering such services; that is, nonsmokers tend to engage in a significantly higher frequency of patient counseling than current smokers do. 12,13 Moreover, few published studies have discussed this complex issue and examined whether common cessation methods that might work with the general population can be generalized to physicians. 14,15…”
Section: Introductionmentioning
confidence: 99%